Pengaruh Pemanfaatan Teknologi Informasi Dan Sumber Daya Manusia Terhadap Ketepatwaktuan Pelaporan Keuangan Pemerintah Daerah - Mona Mokodompit; Hustianto Sudarwadi; Shenyta Denofi Kurniawati (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2019)
The study aims to determinen: (1) the influence of the use of information technology on the timeliness of local government financial reporting, (2) human resources on the timeliness of local government financial reporting. This type of research is quantitative research. The population in this study is the number of staff of regional (OPD) in Manokwari regency totaling 1.925 which are devided into 27 OPD. The sampling technique wed 331 random sampling and individuals using the slovin formula. This type of research data is primary data, this study use data collection techniques by distributing questionnaires to respondent, while the primary data source in this study is obtained from respondents’ answer to the questionnaires distributed to respondents’ namely employes OPD. The result of the study conclude that: the use of information technology and human resources has a significant positive effect on the timeliness of local government financial reporting.